2017
DOI: 10.5897/ijnam2017.0218
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of double burden of malnutrition and its associated factors among selected in-school adolescents: Evidence from South Ethiopia

Abstract: The coexistence of both under nutrition and over nutrition or known as double burden of malnutrition (DBM) is a recent emerging nutritional problem documented in most developing countries. In Ethiopia, though there are various studies documenting the magnitude of under-five children nutritional problem, there is a research gap on DBM among adolescents. To fill the identified gap, the extent of the problem among in-school adolescents was assessed. A school based, cross-sectional study was conducted among 634 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
10
2
Order By: Relevance
“…This study showed that 32.2% of school adolescent girls were underweight. This magnitude is higher as compared to other studies conducted in Arsi Zone ( [8,[12][13][14][15][16][17][18][19][20][21][22][23][24]. This might be due to the low socioeconomic status in this study area.…”
Section: Discussioncontrasting
confidence: 55%
“…This study showed that 32.2% of school adolescent girls were underweight. This magnitude is higher as compared to other studies conducted in Arsi Zone ( [8,[12][13][14][15][16][17][18][19][20][21][22][23][24]. This might be due to the low socioeconomic status in this study area.…”
Section: Discussioncontrasting
confidence: 55%
“…The prevalence of thinness, stunting, and overweight/obesity were 11.6%, 15.6%, and 7.1%, respectively. The current prevalence of thinness and stunting is lower compared to many studies done in the country 22 -26 as well as in Africa: Tanzania (21%), Kenya (15.6%) and Nigeria (24.2%). 42 -44 More specifically, the stunting prevalence was much lower than what was documented in many studies in Ethiopia.…”
Section: Discussionmentioning
confidence: 64%
“…21 Studies on adolescence nutrition and its context-specific predictors in a cash crop farming setting of Ethiopia are not available so far. Pocket studies in the general population showed a prevalence of thinness among adolescents, ranging from 19.7% to 83%, 22 -26 stunting of 16% to 28.5%, 22 -24 and overweight or obesity of 2.0% to 16.7%. 26 -30 Gender, age, residence, and educational status of the adolescent as well as their parents, age of the child, household wealth index, and family size were the most commonly reported socioeconomic determinants in the above studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the full texts of 50 remaining records for eligibility, and 28 records were further excluded by the inclusion and exclusion criteria. Finally, 22 studies were considered for the final review and meta-analysis [7,[12][13][14][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (Fig. 1).…”
Section: Study Searches and Selectionmentioning
confidence: 99%